Airway and Parenchymal Strains during Bronchoconstriction in the Precision Cut Lung Slice - Hiorns, Jonathan E.; Bidan, Cécile M.; Jensen, Oliver E.; Gosens, Reinoud; Kistemaker, Loes E. M.; Fredberg, Jeffrey J.; Butler, Jim P.; Krishnan, Ramaswamy; Brook, Bindi S. (Frontiers in Physiology, 2016)
The precision-cut lung slice (PCLS) is a powerful tool for studying airway reactivity, but biomechanical measurements to date have largely focused on changes in airway caliber. Here we describe an image processing tool that reveals the associated spatio-temporal changes in airway and parenchymal strains. Displacements of sub-regions within the PCLS are tracked in phase-contrast movies acquired after addition of contractile and relaxing drugs. From displacement maps, strains are determined across the entire PCLS or along user-specified directions. In a representative mouse PCLS challenged with methacholine, as lumen area decreased, compressive circumferential strains were highest in the 50 microns closest to the airway lumen while expansive radial strains were highest in the region 50-100 microns from the lumen. However, at any given distance from the airway the strain distribution varied substantially in the vicinity of neighboring small airways and blood vessels. Upon challenge with the relaxant agonist chloroquine, although most strains disappeared, residual positive strains remained a long time after addition of chloroquine, predominantly in the radial direction. Taken together, these findings establish strain mapping as a new tool to elucidate local dynamic mechanical events within the constricting airway and its supporting parenchyma.